Adaptive Fahrhinweise für ein längsdynamisches Fahrerassistenzsystem zur Steigerung der Energieeffizienz - Dörr, Dominik (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2021)
In this work, the author developed driver advices, that help the driver to perform his driving task in an efficient way. This advices are classified as a driver assistance system. They have been implemented and their influence on the driver has been investigated during a case study.